Highlights of clinical and laboratory parameters among severe COVID-19 patients treated with tocilizumab: a retrospective observational study - Şener, Melahat Uzel; Çiçek, Tuğba; Öztürk, Ayperi (São Paulo Medical Journal, 2022)
BACKGROUND: Coronavirus disease 2019 (COVID-19) can cause cytokine release syndrome (CRS), which leads to high mortality rates. Tocilizumab suppresses CRS by blocking the signal transduction of interleukin-6 (IL-6). OBJECTIVE: To evaluate the clinical and laboratory parameters associated with mortality among patients receiving tocilizumab treatment. DESIGN AND SETTING: Retrospective observational study conducted in the chest disease departments of two different training and research hospitals in the center of Ankara, Turkey. METHODS: Patients who were hospitalized and treated with tocilizumab in September 2020 were retro-spectively analyzed. Their laboratory parameters and clinical characteristics were obtained from the hospital information system database. Comparative analyses were performed between the patients who died and the ones who survived. RESULTS: A total of 58 patients who received tocilizumab treatment were included in this study, among whom 35 (60.3%) died. There was no difference between the mortality and survival groups in terms of white blood cell (WBC), neutrophil, lymphocyte, ferritin or C-reactive protein (CRP) levels detected on admission. WBC, lymphocyte, neutrophil and CRP levels measured on the third and fifth days after tocilizumab administration were found to be significantly lower in the survival group (P < 0.05). In multiple logistic regression analysis, age and oxygen saturation were determined to be independent risk factors for mortality. CONCLUSION: Persistently high WBC, CRP and neutrophil levels and low lymphocyte levels could be considered to be valuable indicators of mortality among COVID-19 patients treated with tocilizumab. Age and low oxygen saturation are independent risk factors for mortality among patients receiving tocilizumab treatment.